(untitled) (MMIT Proceedings, 2024)
The article discusses current trends and challenges in online education, which have become particularly significant in light of the global pandemic. It emphasizes the importance of teacher training and student support in distance learning in order to maintain the quality and authenticity of the learning experience. The article analyzes the potential advantages and prospects of online education and provides recommendations for overcoming obstacles to its successful implementation.